MİLLÎ EDEBİYAT DÖNEMİNDE ULUSAL BİLİNCİN İNŞASI - YILDIRIM, FARİZ (Fırat Üniveristesi, 2019)
Milliyetçiliğin esasında bir kültür ve kimlik üretim işi olması, kültürel aygıta, özellikle de edebiyata millî kimlik inşa sürecinde fert ve toplumun algı ve ilgisinin uyandırılması ve bunun kollektif belleğe dönüştürülmesi noktasında ayrıcalıklı bir mevki kazandırmıştır. Edebiyatın imkan ve potansiyelinin ulus kimliğinin inşasına hasredilmesi yahut bu alanda kullanılmasıyla ortaya çıkan yazın tür ve akımını ifade eden millî edebiyatın bütün ulusçuluk deneyimlerine öncülük ve refakat etmesinin temel gerekçesi budur. Nitekim bu çalışma da Türk milliyetçiliğinin inşa sürecine edebiyatın bu anlamdaki dahlini araştırma konusu yapmıştır. Tezin bu bağlamdaki araştırma plan ve önceliği çerçevesinde ilkin milliyetçiliğe ideolojik perspektiften yaklaşılarak teorik bir çerçeve üretilmiştir. İkinci aşamada Türkçülüğün ortaya çıkışı ve gelişim evreleri ele alınarak Tanzimat ve Millî Edebiyat Dönemi Türkçülüğünün genel karakteristiği belirlenmiştir. Tezin son ve esas bölümünde ise Yeni Lisan'ın kanonik düsturlarıyla gerçekleştirilen kültürel üretimin inşa sistematiği otaya çıkarılmıştır. Anlatılarda tekrar eden imge ve izlekler; öteki, gaflet/uyku ve dönüş izlekleri şeklinde kategorize edilmiştir. Öteki başlığı altında öteki söylem ve algısının Türklük bilincinin oluşumundaki sosyopsikolojik etkileri, gaflet imgelerinde uyanış programı, dönüş izleklerinde ise millî benliğin eriştirici ve eğreti izlekleri bahse konu edilmiştir. Ulus inşası, bütün toplumsal dinamiklere ve hayata nüfuz etmeyi gerektiren bir süreçtir. Türk milliyetçiliğinin güdümündeki Millî Edebiyat anlatısının da bu anlamda bütün sosyokültürel ve politik süreçleri kuşatan yaklaşımlar ileri sürdüğü ve hayatı bütünüyle yenilemeye yönelik bir inşa stratejisiyle hareket ettiği görülmüştür. Bunun neticesinde de modern bir Ergenekon süreci yaşayan Türklüğe, yeni bir hamle gücü ve var oluş bilinci kazandırmayı başarmıştır.

The fact that nationalism is essentially a process of culture and identity formation has given it a privileged position in the process of national identity construction process, related to the arousing of the perception and interest of the individual and society towards cultural tool, especially literature, and its transformation into collective memory. This is also the main reason for national literature, meaning either the devotion of possibilities and potential of literature to the construction of the national identity or the genres and movements that emerge in this field, to lead and accompany all nationalist experiences. As a matter of fact, the research object of this study is the influence of literature on the process of the construction of Turkish nationalism in this sense. Within the framework of the research plan and priority of this thesis, first of all, a theoretical framework has been produced by approaching nationalism from an ideological perspective. In the second stage, examining the emergence and development phases of Turkism, the general characteristics of Tanzimat and Turkism of National Literature Period has been determined. In the last and main part of the thesis, the structure systematic of the cultural production, generated by the canonical principles of the New Language, has been elicited. Repeating images and themes in the narratives has been investigated by positioning on a three-legged strategy involving the other, negligance / sleep and recovery. Under the title of "other," socio-psychological influences of the discourse and perception other in the formation of Turkish consciousness has been mentioned. As for the theme of recovery, the transporting and extrinsic themes of national self has been the subject matter. The construction of the nation is a process that requires penetration into all social dynamics and life. In this sense, it is seen that the National Literature narration under the control of Turkish nationalism puts forwards approaches that embrace all sociocultural and political processes, and acts with a building strategy that completely aims to renew the life. Consequently, National Literature has achieved to raise the consciousness of a community, at the edge of political and cultural destruction, and provided them the power of retreat.
The construction of national consciousness in national literature period
Keywords: Türk Dili ve Edebiyatı